Optimization of Heat Exchange in a Heat Accumulator with Latent Heat Storage. (2015) - Constantin, Luca; Dragomir-Stanciu, Daniel; Crismaru, Ionut Vasile
Abstract: The paper analyzes the possibility to optimize the construction of a heat exchanger, which has the role of thermal accumulator in a solar energy storage system for residential use. The storage of solar energy is made in a phase change material (PCM), namely wax paraffin. Starting from a model of thermal accumulator tested experimentally, aiming at improving the heat transfer between wax paraffin and water takes the heat stored. For the new construction solutions proposed heat transfer modeling was performed, using Fluent module from ANSYS 14.5.